Lignocellulosic Recycled Materials to Design Molded Products: Optimization of Physical and Mechanical Properties - Aguerre, Yanina Susel (2016)
The object is to contribute to the reduction of environmental pollution, by reusing a fraction of urban solid waste, forestry and agroindustrial waste: newspaper (ONP), office paper (OWP), corrugated cardboard (OCC), pine sawdust, eucalyptus sawdust and sugar cane bagasse as raw material to design biocontainers suitable for growing plants, by applying pulp molding technology. The purpose is to evaluate the effects of the combination of these lignocellulosic materials on the physical-mechanical properties and optimize responses in order to select an ideal mixture on basis the product?s necessities. An experimental design of type mixture of extreme vertices was followed, considering secondary fibers as base material, in a 0-100% proportion, and pine sawdust, eucalyptus sawdust and bagasse fibers as reinforcement, in a 0-40% proportion. An experimental matrix by each reinforcing material was proposed. Properties were evaluated: density, tensile, bursting, tearing, compression, stiffness, wet tensile, permeability and water retention, testing handsheets weighing 150 g/m2. Responses were optimized using a statistical program. It was found that OWP pulps increase strength properties; OCC pulps increases tear and wet tensile; ONP pulps increase stiffness and reinforcement materials increase permeability. Factors that allow reaching the objectives are a mixture of pulp OWP/OCC in a 50/50 proportion.